474 Increasing the Availability of Operation Notes at Hand Surgery Follow-Up Through the Use of Electronic Operation Notes. (4th May 2021) - Macneal, P; Brar, S; Dassanayake, S; Jones, K; Ghareib, A; Moledina, J
Abstract: Introduction: The availability of operation notes is crucial to provide high-quality post-operative care. This clinical audit evaluates the availability of operation notes at post-operative follow-up, in a Tertiary Hand Unit, before and after implementation of electronic operation notes. Method: This was a prospective audit analysing the availability of operation notes at the first post-operative hand surgery appointment. The initial data collection was over a 6-week period (July – August 2019). Following this, a standardised electronic operation note template was created in line with BSSH Hand Trauma Guidelines and RCS Good Surgical Practice. Six months later, a re-audit was conducted over a 4-week period (March 2020). Results: The initial audit included 104 adult patients, with operation notes available for 64% (n = 67) of patients, and 94% (n = 63) of those were in paper format. Following implementation of electronic operation notes, the re-audit included 53 adult patients. For these patients, 96% (n = 51) of their operation notes were available, and 96% (n = 49) of the operation notes were electronic. Conclusions: These findings demonstrate that electronic operation notes greatly increased the availability of operation notes at follow-up This innovation has significant implications for upholding well-coordinated continuity of care for patients undergoing surgery.